Ronald Storrs and Mısırlızade Necati: The Governor's encounter with the 'Thirteenth Greek' - Nevzat, Altay (My University, 2011)
Relations between British colonial administrators and the Turkish Cypriots are commonly portrayed purely through the rigid framework of subservience and collaboration. Furnishing evidence through a micro-historical study of the relationship which developed in the late 1920s between Governor Ronald Storrs and Turkish Cypriot political leader Mi{dotless}si{dotless}rli{dotless}zade Necati, the paper proposes that this familiar portrayal is misleading and overlooks significant cases of conflict between the British authorities and prevailing Turkish Cypriot political forces. The argument is supported by a wider analysis of the two men's formative experiences and in particular of the 'public school spirit' inculcated in Storrs as invariably in other British administrators also. Based upon such analysis it is suggested that such dispute went beyond the solely personal and that the conflictual relationship that arose in this instance was largely a consequence of the colonial inability to adequately adapt to the novel force of Kemalist nationalism in Cyprus.
Keywords: British imperialism; Colonialism; Cyprus; Education; Kemalism; Nationalism; Turkish Cypriots